Hubungan Nilai Treshold dengan KadarAngiotensin Converting Enzyme-2 - Sabar Hutabarat; Eti Yerizel; Aisyah Elliyanti; Yulia Iriani (Majalah Kedokteran Andalas, 2023)
Introduction: The coronavirus disease-19 (COVID-19) pandemic has been a major problem in every country worldwide. Cases of  COVID-19 in children are usually caused by exposure to infected family members or other adults infected with the disease. Clinical manifestations in children vary widely from symptomatic to asymptomatic. This study aims to determine the relationship between cycle threshold (Ct) value with Angiotensin Converting Enzyme-2 (ACE-2) Method: This study is an observational study with a cross-sectional design. The purpose is to analyze the relationship between Ct value with ACE-2, IL-6, IL-10 level in asymptomatic COVID-19 pediatric patients. Ct value measured using RT-PCR and ACE 2,  Il-6 and IL-10 were measured using ELISA examinations. Result: Mean of ACE-2 is 132,66 ± 38,19 pg/mL (21,63 – 171,63 pg/m). Conclusion: The majority of Ct value in asymptomatic pediatric COVID-19 patients were high (85,7%). Statistically, there was no significant correlation between Ct value with ACE-2, IL-6 and IL-10 in COVID-19 asymptomatic children. Keyword: Angiotensin Converting Enzyme-2, Covid-19 Asymptomatic Children